Does human activity impact the natural antibiotic resistance background? Abundance of antibiotic resistance genes in 21 Swiss lakes. (August 2015) - Czekalski, Nadine; Sigdel, Radhika; Birtel, Julia; Matthews, Blake; Bürgmann, Helmut
Abstract: Antibiotic resistance genes (ARGs) are emerging environmental contaminants, known to be continuously discharged into the aquatic environment via human and animal waste. Freshwater aquatic environments represent potential reservoirs for ARG and potentially allow sewage-derived ARG to persist and spread in the environment. This may create increased opportunities for an eventual contact with, and gene transfer to, human and animal pathogens via the food chain or drinking water. However, assessment of this risk requires a better understanding of the level and variability of the natural resistance background and the extent of the human impact. We have analyzed water samples from 21 Swiss lakes, taken at sampling points that were not under the direct influence of local contamination sources and analyzed the relative abundance of ARG using quantitative real-time PCR. Copy numbers of genes mediating resistance to three different broad-spectrum antibiotic classes (sulfonamides: sul1, sul2, tetracyclines: tet(B), tet(M), tet(W) and fluoroquinolones: qnrA ) were normalized to copy numbers of bacterial 16S rRNA genes. We used multiple linear regression to assess if ARG abundance is related to human activities in the catchment, microbial community composition and the eutrophication status of the lakes. Sul genes were detected in all sampled lakes, whereas only four lakes contained quantifiable numbers of tet genes, and qnrA remained below detection in all lakes. Our data indicate higher abundance of sul1 in lakes with increasing number and capacity of wastewater treatment plants (WWTPs) in the catchment. sul2 abundance was rather related to long water residence times and eutrophication status. Our study demonstrates the potential of freshwater lakes to preserve antibiotic resistance genes, and provides a reference for ARG abundance from lake systems with low human impact as a baseline for assessing ARG contamination in lake water. Highlights: 21 Swiss lakes were surveyed for abundance of 6 antibiotic resistance. Gene abundance data was related to catchment data from a GIS database. Wastewater input was identified to influence sul1 resistance gene abundance. sul2 abundance was influenced by several estimators of human impact. Study sets a baseline for background abundance of resistance genes in lakes.